Toxic Truth: Lead and Fertility - Karen Clay; Margarita Portnykh; Edson R. Severnini (Institute of Labor Economics (IZA), 2018)
Using U.S county level data on lead in air for 1978-1988 and lead in topsoil in the 2000s, this paper examines the impact of lead exposure on a critical human function with societal implications – fertility. To provide causal estimates of the effect of lead on fertility, we use two sets of instruments: i) the interaction of the timing of implementation of Clean Air Act regulations and the 1944 Interstate Highway System Plan for the panel data and ii) the 1944 Interstate Highway System Plan for the cross sectional data. We find that reductions in airborne lead between 1978 and 1988 increased fertility rates and that higher lead in topsoil decreased fertility rates in the 2000s. The latter finding is particularly concerning, because it suggests that lead may continue to impair fertility today, both in the United States and in other countries that have significant amounts of lead in topsoil.
Keywords: Q53; J13; N52; N92; 330; lead in air; lead in gasoline; lead in topsoil; fertility; Clean Air Act